Physicochemical and quality characteristics of New Zealand goat meat and its ultrastructural features. (November 2022) - Gawat, Mariero; Kaur, Lovedeep; Singh, Jaspreet; Boland, Mike
Graphical abstract: Highlights: Goat meat raw longissimus thoracis and semimembranosus muscles had low intramuscular fat (<2%) regardless of breed. Variation in goat meat texture is influenced by pH and collagen content and is highly dependent on muscle type. Raw meat from feral and Boer cross goats can be differentiated in color based on their redness values. TEM images revealed that existing commercial processing for post-mortem handling of goat meat results in muscle cold-shortening. Abstract: This study investigated the quality characteristics, physicochemical indexes and ultrastructure of New Zealand goat meat. The goat meat samples were sourced from New Zealand feral goats and Boer crossbreeds. Raw longissimus thoracis (LT) and semimembranosus (SM) muscles were evaluated after 48 hr of post-mortem storage at 4 °C. The cooked meat characteristics were studied after sous vide cooking at 60 °C for 6 h. Meat samples from both goat breeds exhibited intermediate pH values in the range of 5.76 and 5.98. Feral goat meat had higher collagen with lower solubility compared to Boer crosses. All the samples had high peak shear force from 62.1 to 87.3 N, and the variations were highly influenced by pH (p < 0.01) and collagen content (p < 0.05) and are dependent on muscle type (p < 0.01). For color, meat from feral and Boer varies significantly for redness (p < 0.01). Transmission electron micrographs from all samples revealed short sarcomeres ranging from 1.4 to 1.8 µm. Some super contracted muscle fibers were also observed, suggesting that muscles have undergone severe cold-shortening. Our findings indicate that regardless of genotype, the challenge for goat meat quality is its inherently high pH and its susceptibility to cold-shortening that impacts its technological properties.